2020
DOI: 10.1101/2020.11.03.367623
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Automated AI labelling of optic nerve head enables new insights into cross-ancestry glaucoma risk and genetic discovery in over 280,000 images from the UK Biobank and Canadian Longitudinal Study on Aging

Abstract: Cupping of the optic nerve head, a highly heritable trait, is a hallmark of glaucomatous optic neuropathy. Two key parameters are vertical cup-to-disc ratio (VCDR) and vertical disc diameter (VDD). However, manual assessment often suffers from poor accuracy and is time-intensive. Here, we show convolutional neural network models can accurately estimate VCDR and VDD for 282,100 images from both UK Biobank and an independent study (Canadian Longitudinal Study on Aging), enabling cross-ancestry epidemiological st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 72 publications
(110 reference statements)
0
3
0
Order By: Relevance
“…Lastly, in the time since data collection, more CDR SNPs have been identified. 21 A larger CDR SNP panel might yield different results.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, in the time since data collection, more CDR SNPs have been identified. 21 A larger CDR SNP panel might yield different results.…”
Section: Discussionmentioning
confidence: 99%
“…Glaucoma is associated with elevated IOP, whereas the ONH is heavily affected by the biomechanical forces due to elevated IOP and is therefore susceptible to structural damage and the associated functional loss. Han et al trained a convolutional neural network (CNN) model on a large dataset of 282,100 images from both the UK Biobank and the Canadian Longitudinal Study on Aging -CLSA for automatic AI labeling of the ONH (15). Their study was able to extract two key ONH parameters: vertical cup-to-disc ratio and vertical disc diameter.…”
Section: Optic Disc and Optic Nerve Head Abnormality Detection In Gla...mentioning
confidence: 99%
“…In another study, a genome-wide meta-analysis identified 127 open-angle glaucoma loci (23). AI-driven algorithms can also be used for assigning vertical cup-to-disc ratios to extend our knowledge about the genetic architecture of glaucoma (15). Such findings may guide the development of novel transgenic mouse models that are highly relevant to the human disease process.…”
Section: Genotype-associated Genomic Risk For Glaucomamentioning
confidence: 99%